Methods of Increasing Productivity of Material Layerwise Synthesis Based on Melting Wire Filler by Electric Arc in Vacuum - Nikolaevich Trushnikov, Dmitriy; Dmitrievich Shchitsyn, Yuri; Sergeevich Belinin, Dmitry; Bezukladnikov, Igor; Reisgen, Uwe; Georgieva Koleva, Elena (International Journal of Engineering and Technology, 2018)
Prospects of one of unconventional research areas aimed at improving additive technologies have been described. The key aspect of the proposed technology is the formation of multilayered homogeneous materials in vacuum using electric arc as a heating source, as well as using a solid metal wire as a filler metal. It is shown that this approach, compared to the available solutions applied in the global industrial production practices, will serve to increase productivity related to forming layerwise materials, as well as to resolve a number of disadvantages of the available equipment used for additive technologies implementation.Â Â